To remember to remember reflections on the literary memoirs of Filipino women - Hidalgo, Cristina Pantoja 1944- (University of Santo Tomas Publishing House, 2015)
"This book picks up a story which the author began to tell in 1994, with her groundbreaking study of the autobiographical narratives of Filipino women, "Filipino Woman Writing" (Second Edition, UST Publishing House, 2015). Here, Cristina Pantoja Hidalgo, a much-awarded writer of fiction and nonfiction, literary scholar, teacher and mentor to numerous younger writers, turns to the first women writers to own the name "literary memoirist. Four generations of women writers are represented in this unusual volume which is itself both creative nonfiction and literary study: Paz Policarpio-Mendez (b. 1903); Solita Camara-Besa (b. 1915); Gilda Cordero-Fernando (b. 1930); Merlie Alunan (b. 1943); Criselda Yabes (b. 1964); Jenny Ortuoste (b.1968); and Rica Bolipata-Santos (b. 1969). Fascinating as the differences among them are, the things they have in common are equally striking. And, above all else, what they have in common is that they are-in their different ways-one and all, transgressive. Hidalgo shows how these writers have crafted stories from memories that continue to haunt them, using language whose shapeliness transform them into compelling experiences for their readers. They have taken a long, hard look at their little corners of the world, and brought them to life for their readers: small provincial town and big, glittering city; bohemian enclave; seedy old racetrack; and university campus. In the course of telling of their past, they have, as Nancy Ballard puts it, gathered meaning from that past and thrust it forward into the present, that they might serve readers as they negotiate the unknown, perilous future."--Back cover.